Evaluation of Hospital Treated Wastewater on Seed Germination and Plant Growth Indices - Fathollah Gholami-Borujeni; Atefeh Zahedi; Masumeh Sheikhi (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: Effluent of wastewater treatment plant after reaching to the standards is commonly used as the source of irrigation in agriculture in many developing and developed countries. Before using wastewater in agriculture, it is better to evaluate the phytotoxic effects of wastewater on crops. Therefore, the main objective of this study was to evaluate the impacts of raw and treated hospital wastewater on seed germination and growth parameters of selected vegetable species. Methods: In this study, the toxicity effects of different concentrations (i.e., 0%, 10%, 30%, 50%, 70%, and 10% v/v) of raw and treated hospital wastewater on seed germination, root growth, as well as stems and leaves of three vegetables, namely Coriandrum sativum, Anethum graveolens, and Lepidium sativum, using Petri dish cultivation method were studied through three replications in a completely randomized design. The parameters, such as germination percentage, germination rate index, and growth parameters (i.e., the length of the root, shoot, and leaf), were calculated after 0-10 days. In addition, Biochemical Oxygen Demand, COD (Chemical Oxygen Demand), Toxic Shock Syndrome, pH, Total Dissolved Solids, EC (Electrical Conductivity), free chlorine residual, and microbial quality of wastewater were analyzed in the present study. Results: Obtained results showed that no significant relationship was observed between the control, as well as raw and treated wastewater samples, in seed germination capacity. According to the finding, the length of the root, shoot, and leaf increased with an increase in the concentration of wastewater. Therefore, hospital wastewater had no negative effect on the seed germination of the plants. Conclusion: Hospital wastewater can contain hazardous substances, such as pharmaceutical residues, chemical hazardous substances, pathogens, and radioisotopes. In this regard, it is required to investigate more qualitative parameters regarding the reuse of hospital wastewater in agriculture.